How bank managers assess small business borrowers? - Mahmood, Rosli; Abd Rahman, Ghazali (Malaysian Institute of Management, 2007)
The purpose of this study is to develop an understanding of the decision making process which bankers follow in granting loans to the small business borrowers. A mail survey technique was employed, and questionnaires were administered on bank branch, managers of domestic banks.A total of 138 useable questionnaires were received, representing a 13.8 percent return rate.The findings reveal that intended purpose of loan, repayment of previous loan and loan activity at other banks were ranked as the top, criteria in the credit assessment of small business borrowers.On the hand, government guarantee of loan, CVs of clients and charge on assets were given lowest ranks in terms of importance.The salient factors identified in this study also indicate that the bank managers focused on risk when dealing with the small business borrowers.